Impact of fear on pediatric pain assessment: A retrospective study - Myriam Aïche; Jean Toniolo; Emilie Auditeau; Stéphanie Thurillet; Laurent Fourcade (PLoS ONE, 2025)
Background Fear and pain are intimately linked in the experience of caring for a child. The advent of a self-assessment tool for fear makes it possible to study the link between these two emotions. Objectives The primary objective was to determine whether self-assessment of fear (with the Trouillomètre®) affects self-assessment of pain. The three secondary objectives were to search for a correlation between fear and pain scores, and to analyze the effect on analgesic consumption and tool satisfaction. Methods A retrospective study was carried out in a French university hospital comparing the VAS (visual analogue scale) values of children aged 7–12 presenting to pediatric ED before and after the introduction of a fear assessment by Trouillomètre®. Selected pain scores were measured using the VAS. Analgesic consumption was compared between the exposed and unexposed periods. Satisfaction was assessed using a questionnaire distributed to the paramedical team. Results 154 patients in the Trouillomètre® group and 154 in the unexposed group were included in the analysis. There was no significant difference between the 2 groups in terms of pain assessment, but there was a significant correlation between fear and pain (rho = 0.18, p-Value = 0.002). Following the implementation of the tool, there was an increase in level 1 analgesic use and a corresponding decrease in level 2 analgesic use. The paramedical teams were satisfied with the tool. Conclusion This study did not show any impact of fear assessment on pain assessment, but secondary analyses suggest that there is an effect of fear management on pain already described in the literature, and that Trouillomètre® can be used to highlight this fear for its better management.